(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
The article analyzes the play Oratorium, by the German group She She Pop, and how it seeks to bring the Brechtian model of Lehrstück into a contemporary political scene, discussing one of the most urgent themes of Berlin society today: the question of housing. Thus, we examine how certain post-dramatic and comic theater finds in “not-knowing” an emancipatory potential.